Stabilizing the rouble: Is there a case for a new Fisher rule? - Friedrich L. Sell (Intereconomics, 1995)
The management of the exchange rate by the Russian authorities obviously lacks both effectiveness and efficiency. “Black Tuesday” has vividly shown how vulnerable the rouble is to speculative attacks. In this article, a “classical” proposal is evoked and is discussed as an alternative to the present exchange-rate policy from the sustainability point of view.
Keywords: 330; Exchange-Rate Policy